Computational Fluid Dynamics Simulation to Determine Combined Mode to Conserve Energy in Refrigerated Vehicles. Issue 2 (26th March 2015) - Han, Jia‐Wei; Zhao, Chun‐Jiang; Yang, Xin‐Ting; Qian, Jian‐Ping; Xing, Bin
Abstract: In this work, to improve the rate at which cool air ventilates the tail of a refrigerated compartment and thereby reduces the temperature difference between the front and rear of the cargo area, we increase the length of an air conduit in the direction of the air outlet of the refrigerating unit. In addition, minimizing the cooling time during transportation reduces energy consumption and improves the economics of cold‐chain transport. To address this problem, we created a three‐dimensional computational fluid dynamics model of a transport compartment and used potatoes as test cargo. The unsteady shear stress transport κ ‐ ω model was adopted to simulate air flow and heat transfer inside the compartment. The results show that the additional air conduit inside the compartment should significantly improve the spatial uniformity of the temperature inside the cargo area. The results of the simulation are consistent with experiments. Practical Applications: Although cold‐chain transport must ensure a constant low‐temperature environment for perishable foods, more important is the requirement to maintain temperature uniformity in the cargo area. This is the basis by which the quality, safety and shelf life of perishable food are ensured. In this study, we have investigated how to minimize the cooling time during transportation in order to reduce energy consumption and improve the rate at which cool air ventilates the tail of a refrigerated compartment. This research provides reliable theoretical arguments for enhancing temperature uniformity in the cargo enclosure of refrigeration trucks and for reducing unnecessary energy consumption during transportation.